PENGARUH DISIPLIN DAN PROFESIONALISME KERJA TERHADAP KINERJA KARYAWAN PT BENTENG PURWA PUTRA CABANG SUKABUMI - Agustin, Fitrania (Jurnal Ilmu Manajemen Retail Universitas Muhammadiyah Sukabumi, 2024)
This study aims to examine and analyze the Effect of Discipline and Work Professionalism on Employee Performance at PT. Benteng Purwa Putra Sukabumi Branch. This research method uses a quantitative descriptive method, namely by describing and exposing the variables studied and then drawing conclusions. The object of research that becomes the independent variable is Work Discipline (X1) and Work Professionalism (X2) and Employee Performance (Y) is the dependent variable. Data collection techniques carried out in this study were 54 people or respondents and data collection techniques using Likert Scale measurements. The results of this study are used in the determination coefficient test, there is an influence of 47.8% of work discipline and professionalism on employee performance, while the remaining 52.2% is influenced by other factors. Therefore, based on the F hypothesis test, it can be concluded that the hypothesis is accepted, which means that the influence of work discipline and professionalism on employee performance has a simultaneous effect. Where Fcount is 25.223 > 2.79 with a sig. 0.000 < 0.05.